SOCIAL STUDIES EDUCATION: A STARTINGPOINT TO REFLECT ON THE MENANCE OF CUMULATIVE SOCIAL FAILURES AND POOREDUCATION IN NIGERIAN SCHOOLS - U.K Emoefe Ekiugbo:P.h.D (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Quality represents an acceptancenorm or an essentialcharacteristicsthat gives identity or credibility to something.With reference to education, quality refers to the highest or finest stands to be pursued,a sort of degree of excellence to be aimed at.Nigeria , a country that holds a strategic place on the Africa continent, adiplomatic force in West Africa, a major player in world politics with enormous potentials for economic and social development is faced with myraids of problems ranging from political gangsterism, ethnicmilitancypoaching of maritime resources, illegal drugs dealing,repaciouscorruption, financial mismanagement are allmanifestationof failure of national security.Nigeria is currently entangled in the web of combustible lingering ethnic and religious conflicts. This has brought to limelight the issuepersisting state failure and enormous institutional decayin the country. This quickly festered in hydraheadeddimensionas frequent attacks on schools, compounding the problems associated with education in Nigeria.The study is an attempt to x-ray the extentof such failuresin the economy and the impact on the quality of education in the country, using the social studies classroom.Recommendations were made to the Nigerian government that have come under attack over theluckstreperformances andhowthe situation can be improved.